Social networks : encouraging collaboration among first year undergraduate students at the University of Cape Town - Mwanza, Gabriel (School of Education, 2015)
The study seeks to gain a rich and in-depth understanding of the nature of students learning, mediated by their participation insocial networks in three learning locations at the University of Cape Town (UCT), namely, (i) formal learning locations, such as scheduled classes and laboratory sessions; (ii) semi-formal learning locations, such as libraries, walk-in laboratories and mingling areas; and (iii) informal learning locations, such as after-hours work, university residences, and weekends in private homes.